2021
DOI: 10.1002/mnfr.202000834
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Uptake of Processed Bovine β‐Lactoglobulin by Antigen Presenting Cells: Identification of Receptors and Implications for Allergenicity

Abstract: Scope: -lactoglobulin (BLG) is a major cow milk allergen encountered by the immune system of infants fed with milk-based formulas. To determine the effect of processing on immunogenicity of BLG, this article characterized how heated and glycated BLG are recognized and internalized by APCs. Also, the effect of heat-induced structural changes as well as gastrointestinal digestion on immunogenicity of BLG is evaluated. Methods and results: The binding and uptake of BLG from raw cow milk and heated either alone (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 55 publications
(101 reference statements)
0
20
0
Order By: Relevance
“…Therefore, the presence of casein can interfere in ELISA assays when determining binding of AGE receptors to heated MP. Next to AGEs, it has also been shown that other 3D-structural properties such as hydrophobicity and aggregation of food proteins can result in binding to AGE receptors [2,3,8]. Therefore, the role of the 3D structure of casein in binding to sRAGE was further investigated using dot blot analysis (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the presence of casein can interfere in ELISA assays when determining binding of AGE receptors to heated MP. Next to AGEs, it has also been shown that other 3D-structural properties such as hydrophobicity and aggregation of food proteins can result in binding to AGE receptors [2,3,8]. Therefore, the role of the 3D structure of casein in binding to sRAGE was further investigated using dot blot analysis (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…For both receptors, negative charge, aggregation, and hydrophobicity have been suggested as important determinants for their binding to ligands [3,7]. Moreover, there is evidence in literature that, e.g., sRAGE recognizes high molecular weight ligands formed upon aggregation of proteins [2,8,10]. The hydrophobic elements of the casein molecules are located in the inside of the casein micelle, whereas the negatively charged ends of the κ-casein point to the outside of the micelle [11].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations